Letter book belonging to James Curtis Booth - Booth, James Curtis (1844)
A collection of letters written by James Curtis Booth (1810-1888). Includes material related to a gold-refining patent.
Keywords: Booth, James Curtis, 1810-1888; Gold mines and mining; Metals--Refining; Mineral industries; Gold--Refining; United States Mint; Mint of the United States